TEORI - TEORI DALAM DUNIA PENDIDIKAN MODERN - Temon Astawa, I Nyoman (Jurnal Penjaminan Mutu, 2015)
The theories in education are reflections of both the Renaissance and modern era. In the history of science the discrepancy between the epistemology of the Rationalism, Empiricism, Positivism, and Saintism have become the major interest. The first theory of modern education is the Humanismand the post classical ones which include Behaviorism, Cognitivism, Humanismand Cybernetics.